Measuring health promotion in a sports club setting: a modified Delphi study. (13th November 2019) - Johnson, S; Vuillemin, A; Geidne, S; Kokko, S; Epstein, J; Van Hoye, A
Abstract: Background: The settings-based approach has become an increasing focus in health promotion since the World Health Organization's 1986 Ottawa Charter. Schools and cities have implemented this approach, but development within sports clubs is limited. Thus, an internationally validated measurement of health promotion within this setting is lacking. Methods: A modified Delphi study was completed to develop an international evaluation tool grounded in the settings-based approach. Expert panelists from academia, sports and health sectors were invited to participate in 3 online rounds. Items were generated or selected based on 3 prior Delphi-based studies and 2 nationally validated scales. Round one created a collaborative list of items, round two validated items based on relevance, importance and feasibility and the final round classified items into one of four determinants: cultural, social, environmental or economic. Results: Panelists (69) from 13 countries participated in creating a final list of 62 items at 3 organizational levels. The sports club level included; 5 cultural, 6 social, 6 environmental and 5 economic items. The management level included; 5 cultural, 5 social, 5 environmental and 3 economic items. The coaching level included; 5 cultural, 5 social, 4 environmental and 4 economic items. Conclusions: This study provides three important innovations; 1- it is rooted in theory through the settings-based approach, 2- the measurement tool includes three levels within sports clubs, capturing a whole club dynamic and 3- all items included in the tool have been validated by an international panel of experts. Key messages: This 62-item measurement tool allows the comparison of perceptions from participants, coaches and management regarding how health is promoted within their sports club. This information offers insight on the capacity of sports clubs to implement and monitor policies and practices on the promotion of health beyond sports performance within their organization.